مقارنة النتائج العلاجية لـ سيلودوسين ودوكسازوسين عند مرضى ضخامة الموثة الحميدة - كنعان, محمد; عباس, بسام; طيوب, وليام محمود (Latakia University Journal -Medical Sciences Series, 2014)
يهدف البحث إلى مقارنة النتائج العلاجية لـ سيلودوسين, والـ دوكسازوسين عند مرضى ضخامة الموثة الحميدة. آخذت عينة عشوائية بحجم (67) مريضاً من مراجعي مشفى الأسد الجامعي باللاذقية, وقسّمت إلى مجموعتين: المجموعة الأولى عولجت باستخدام سيلودوسين, والمجموعة الثانية عولجت باستخدام دوكسازوسين. تمّ متابعة التطور العلاجي للمرضى بعد شهر واحد, وثلاثة أشهر, وستة أشهر من العلاج, وتمّ تسجيل القياسات (شدة أعراض ضخامة الموثة, مشعر نوعية الحياة, معدل الجريان البولي الأعظمي) لكلا المجموعتين. وباستخدام الأساليب الإحصائية المناسبة تمّ التوصل إلى النتائج الآتية: 1- فعالية الدوائين سيلودوسين و دوكسازوسين في علاج مرضى ضخامة الموثة الحميدة, حيث أظهرت النتائج العلاجية تحسناً في القياسات (شدة أعراض ضخامة الموثة, مشعر نوعية الحياة, معدل الجريان البولي الأعظمي) وذلك بمرور الزمن. 2- فعالية الدواء سيلودوسين في علاج مرضى الموثة الحميدة, بالمقارنة مع فعالية الدواء دوكسازوسين, حيث أظهرت النتائج العلاجية أن القياسات (شدة أعراض ضخامة الموثة, مشعر نوعية الحياة, معدل الجريان البولي الأعظمي) سجلت تحسناً أفضل لدى المجموعة الأولى التي عولجت باستخدام سيلودوسين لدى مقارنتها بنتائج قياسات المجموعة الثانية التي عولجت باستخدام دوكسازوسين. This research aims to compare the therapeutic results of Silodosin, Doxozosin in patients with Benign Prostate Hyperplasia. A random sample was taken of (67) patients at Assad University Hospital in Lattakia, and was divided into two groups: the first group was treated using Silodosin, and the second group was treated using Doxozosin. We studied the therapeutic development of patients after one month, three months, six months of treatment. Measurements were recorded (Ipss, Qol, Qmax) for both groups. Using appropriate statistical methods, we reached the following results: Equality of the two groups of patients before applying the treatment. The effectiveness of both drugs (Silodosin and Doxozosin) in the treatment of patients with Benign Prostate Hyperplasia, where results showed an improvement in therapeutic measurements (Ipss, Qol, Qmax) by time. The effectiveness of the drug Silodosin in the treatment of patients with Benign Prostate Hyperplasia, compared with the efficacy of the drug Doxozosin, where results showed that therapeutic measurements (Ipss, Qol, Qmax) recorded a better improvement within the first group that was treated using Silodosin when compared with the results of measurements of the second group that was treated using Doxozosin